Japanese management as applied in the Philippines - Tomita, Teruhiko (The Philippine Review of Business and Economics, 1985)
This paper attempts to examine how the Japanese management system is applied in a different social and cultural framework such as that of the Philippines. The outstanding characteristics of the Japanese management system are described, and its economic rationality for Japanese employers and employees, explained. On the basis of survey results which covered top Japanese managers stationed in the Philippines and Filipino managers, the paper examines the basic Japanese management policy and the extent of its modification in the Philippine setting. It includes an evaluation by Filipino middle managers of this modified system. One of its conclusions is that the Japanese management system is welcomed and its durability seems to be assured if the basic aims and goals that motivate and control an immense amount of Filipino behavior and values are met.